Copyrightability of Conceptual Art: An Idea Whose Time Hasn’t Come - Clarida, Bob (The Columbia Journal of Law & the Arts, 2016)
My job really is to kind of throw a wet blanket on the hopes for copyright protection for works of this nature. And that wet blanket has a name, which is 17 U.S.C. § 102(a), and Rob Kasunic, Professor Liu both spoke at some length about this, so I’m not going into it.1 We’ve all read it a thousand times and we all know what it says. It says that works have to be fixed in a tangible medium. That’s in paragraph (a), and then there is a list of types of works of authorship, which “include the following categories,” and as Professor Liu pointed out, the word “include” has basically been read out of the statute. Courts and the Copyright Office basically take the position that if it’s not on this list, it’s not going to be subject to copyright protection. There really is no leeway, I think, in practice at least, for the courts to create new categories of works. So the job often becomes trying to shoe-horn an existing work that doesn’t fit into one of these categories into one of these categories. And that’s not always so easy to do.